2004
DOI: 10.1021/ja037247r
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion NMR Spectroscopy for the Characterization of the Size and Interactions of Colloidal Matter:  The Case of Vesicles and Nanoparticles

Abstract: We report the application of the pulse gradient spin-echo (PGSE) NMR technique (PGSE NMR) to the analysis of large colloidal materials, specifically vesicles formed from macromolecular amphiphiles and nanoparticles. Measurements of size and size distribution were demonstrated to be comparable to those obtained through dynamic light scattering or hydrodynamic chromatography. In comparison to these more common analytical methods, the use of PGSE NMR is particularly advantageous in that, as a spectroscopic techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…Carter et al (2005) characterized air-and water-stable silica nanoparticles by NMR. Diffusion NMR spectroscopy has also been used for the characterization of the size and interactions of colloidal matter (Valentini et al 2004;Carter et al 2005). Lead et al (2000a) used pulsed field gradient NMR to measure the diffusion coefficients of fulvic acids.…”
Section: Spectroscopic and Related Techniquesmentioning
confidence: 99%
“…Carter et al (2005) characterized air-and water-stable silica nanoparticles by NMR. Diffusion NMR spectroscopy has also been used for the characterization of the size and interactions of colloidal matter (Valentini et al 2004;Carter et al 2005). Lead et al (2000a) used pulsed field gradient NMR to measure the diffusion coefficients of fulvic acids.…”
Section: Spectroscopic and Related Techniquesmentioning
confidence: 99%
“…The discrepancy between the DLS results and those from TEM is due to DLS being inherently biased toward larger particles in particle distributions. Valentini et al [81] observed similar discrepancies for polypropylene sulfide nanoparticles dispersed in water.…”
Section: Dynamic Light Scatteringmentioning
confidence: 65%
“…Diffusion NMR spectroscopy has the capability to characterize the size and interactions of colloidal matter [135]. Huang et al studied on the extraction of nanosize copper pollutants such as Cu and Cu 2?…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%